Boundary-layer averaging for standard systems with lag - Efendiev, V. V.; Zheltikov, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The k-th-order asymptotic solution of a standard system with lag is constructed along trajectories calculated according to the averaging scheme of A. N. Filatov. If the perturbation parameter ε ≪ 1, then the use of the step method for finding the solution is connected with cumbersome calculations because the number of required steps is inversely proportional to ε. We suggest another approach in which the step method is used only k times for t [0,k] and justify the asymptotic method.